Validação de métodos laboratoriais aplicados ao diagnóstico de doenças dos animais - Rejane Silva Diniz (2013)
Diagnostic methods applied to veterinary have notorious relevance for diagnosis of diseases of animals, both in the development of research activities and for conducting routine laboratory analysis. The credibility assigned to the results obtained from the laboratory assays depends largely on the validation of the method. A validated method should be confirmed by evaluating and providing evidence that the requirements for a specific intended purpose have been fulfilled. Currently, there are organizations and agencies who publish guidelines and recommendations for this purpose, however, these are not always complete. In addition, such recommendations may differ in some requirements and also the validation parameters even in the case of the same type of diagnostic method. As a result, there is a constant search for the harmonization of standards in order to assure the equivalence of laboratory assays. The objective of this research was to construct a theoretical -methodological validation model of serological methods for laboratory diagnosis of infections of animals. In this research, at first, from the year 2000, were analyzed the recommendations for the development of validation processes for veterinary diagnostic methods, used by 40 countries, among those, 34 current membership and six partners of the Organization for Economic Cooperation and Development (OECD). In a second step, a survey was conducted on the process of development and validation of veterinary laboratory tests in a sample of 38 researchers from 10 Brazilian universities. In the third step was investigated the frequency of validation criteria in articles published in international journals. The results of analyzes indicated that the criteria most often employed in the development and validation of diagnostic methods process were: purpose of the assay and reproducibility (88.9%) and analytical and diagnostic sensitivities and specificities (72.2%). The reference most used in research and validation of tests applied to the veterinarian at the national level was the Manual of Diagnostic Tests and Vaccines for Terrestrial Animals of the World Organisation for Animal Health (OIE). The papers surveyed that were referenced with standards and method validation literature showed a higher frequency (46.3%) of criteria described in this thesis. In conclusion, the OIE Manual of Diagnostic Tests (OIE, 2010) had the highest number of validation criteria, which would generate greater international acceptance of test to be validated. Thus, the use of such document associated with the consultation of specialized scientific articles could potentiate the validation of veterinary tests.